Excitation, ionization, neutralization and anionic production in collisions of C+, N+ and CnN+ (n = 1–3) with He atoms at 2.2 a.u. velocity; cross sections and dissociation branching ratios. (12th September 2019) - Mahajan, T; Béroff, K; Pons, B; Illescas, C; Chabot, M; IdBarkach, T; Launoy, T; Le Padellec, A; Jallat, A; Jorge, A; Aguirre, N F; Diaz-Tendero, S
Abstract: We present measurements of absolute cross sections for projectile ionization and electron capture for C +, N + and C n N + ( n = 1–3) projectiles impinging on He atoms with velocity v = 2.2 a.u. Single and multiple electron processes are considered, as well as projectile dissociative excitation in the case of incident molecular cations. The measurements are compared to Classical Trajectory Monte Carlo (CTMC) calculations for C +, N + + He collisions in the framework of the independent electron approximation. C n N + + He systems are described by means of the independent atom and electron (IAE) model which represents the molecule as a set of independent atoms. The impact parameter probabilities for excitation, ionization and electron transfer in C, C +, N–He collisions, underlying the IAE calculations, are also obtained by means of CTMC computations. A good agreement is generally found between measured and calculated cross sections, except for anionic production of C − and C n N − . The internal energy deposit due to electron excitation in C n N + is also calculated with the IAE/CTMC model and compared to semi-empirical estimates based on either measured dissociation branching ratios for C2 N + and C3 N + (IdBarkach et al 2018 Mol. Astrophys. 12 25) or measured fragments kinetic energy release for CN + . Finally, measured dissociation branching ratios of excited C n N − and C n N Q + species, with 1 ≤ n ≤3 and 0 ≤ Q ≤ 4, are reported.